STRUKTUR KOMUNITAS LAMUN PADA PULAU SARANGBAUNG, KABUPATEN NIAS UTARA - Khairunnisa Khairunnisa; Ahmad Muhtadi Rangkuti; Zufriwandi Siregar; Elisabet Rosevenny Simaremare; Muhammad Riza Kurnia Lubis (Jurnal Kemaritiman: Indonesian Journal of Maritime, 2023)
Seagrass is a coastal vegetation that has various ecological, social, and economic roles for marine biota and humans. However, until now there is little current information regarding the status and inventory Sarangbaung Island which is administratively located in North Nias Regency and geographically located in the Indian Ocean. This study aims to examine the distribution and status of seagrasses in the waters of Sarangbaung Island, North Nias Regency. The research was conducted in December 2022. Observations of seagrass were carried out using the line and square transect method of 0.5 m x 0.5 m which refers to the seagrasswatch method. In total, 3 species were found during this study namely Syringodium isoetifolium, Cymodocea rotundata, and Cymodocea serrulate. Seagrass density on Sarangbaung Island ranges from 53-728 ind/m2. Meanwhile, seagrass coverage is 82%, which indicated that seagrass was in a good category with rich/healthy conditions.